De Hogere Burgerschool: onderwijs en emancipatie - Baneke, David; Maas, Ad (Studium, 2018)
This paper is an introduction to the Studium issue De Hogere Burger School: onderwijs en emancipatie (the Higher Burger School: education and emancipation). Besides introducing the papers of this section, we provide a historiographic outline of this form of education, which was founded in 1863 and played an important role in the emancipation of the Dutch middle classes. The Higher Burger School is also reknowned for its role in the rise of the Dutch natural sciences. In the course of the twentieth century this school gradually became regarded as outdated. IIn 1968 it was replaced by new forms of secondary education.